2021
DOI: 10.30539/ijvm.v45i2.1258
|View full text |Cite
|
Sign up to set email alerts
|

Use of Tannin-Containing Plants as Antimicrobials Influencing the Animal Health

Abstract: The antimicrobial effects of diverse tannin-containing plants, particularly condensed tannins (CTs) produced from various plants, are the subject of this study. CT components can be determined using CT-specific procedures such the HCl-Butanol Acetone assay, Thiolysis reaction, and HPLC/MS analysis. These methods indicate CT contents, including mean degree of polymerization, the procyanidins and prodelphinidins ratio (PC/PD%), the isomers of trans- and cis-, and CT concentration. Tannin-containing plants posses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…It was shown that its antibacterial action was mostly influenced by the kinds of microorganisms found in meat. Although a bacterial Gram-type was not assessed in the current study, our findings might significantly increase the shelf life of beef meat (18,19).…”
Section: Discussionmentioning
confidence: 86%
“…It was shown that its antibacterial action was mostly influenced by the kinds of microorganisms found in meat. Although a bacterial Gram-type was not assessed in the current study, our findings might significantly increase the shelf life of beef meat (18,19).…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, several plant extracts have gained popularity as helpful dietary components in recent years. Grape seed extract (GSE) is high in phenolic components such as monomeric flavan-3-ols, procyanidins, and other chemicals, all of which have antimicrobial and antioxidative properties [21,22]. GSE, on the other hand, has been shown to keep meat fresher for longer dose-dependent periods of time.…”
Section: Introductionmentioning
confidence: 99%